Can [hearts] change minds? Social media endorsements and policy preferences - Pierluigi Conzo; Juan S. Morales; Andrea Gallice; Laura K Taylor; Margaret Samahita (University College Dublin, UCD Centre for Economic Research, 2021)
We investigate the effect of social media endorsements (likes, retweets, shares) on individuals' policy preferences. In two online controlled experiments (N=1,384), we exposed participants to non-neutral policy messages about the COVID-19 pandemic (emphasizing either public health or economic activity as a policy priority) while varying the level of endorsements of these messages. Our experimental treatment significantly shifted the policy views of active social media users by about 0.12 standard deviations. The treatment effect for these users is heterogeneous depending on their pre-existing views. Specifically, message endorsements reinforce pre-existing attitudes, thereby increasing opinion polarization. The effect appears concentrated on a minority of individuals who correctly answered a factual manipulation check regarding the endorsement metrics. This evidence suggests that though only a fraction of individuals pay conscious attention to these metrics, they may be easily influenced by these social cues.
hdl:10197/11939
Keywords: D83; L82; L86; O33; 330; social media; social conformity; political polarization; COVID-19